EUROPEAN ASSOCIATION OF CENTRES OF MEDICAL ETHICS ‒ GENERAL INFORMATION ‒ (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 EACME, in full the European Association of Centres of Medical Ethics, was founded in the early 1980s by a small group of theologians, philosophers and medical doctors who were involved in the new discipline of medical ethics or, as it is now often called, bioethics. These so-called ‘founding fathers’, had the intention to create a network of centres of medical ethics in Europe with the purpose to strengthen the teaching, research, communication and debate on ethical issues in medical practice, health policy and medical sciences. The official starting date of EACME is the 2nd of December 1986 when representatives of six centres came together in Lyon to create this new organisation. The centres (including the Bulletin of Medical Ethics) were located in France (Lyon, Paris), Spain (Barcelona), Belgium (Brussels), the Netherlands (Maastricht) and the United Kingdom (London). The strong presence of clergymen on the original Board was the reason why the EACME has stressed from the start its pluralist approach to bioethical issues. The association expanded in the nineties, when bioethics centres in Europe were increasingly cooperating in research and teaching projects funded by the European Commission. This development was the background for the professionalisation of the young association, strengthened by an efficient organisation and administration under the guidance of the EACME Board and Bureau. New centres joined the organisation, from all over the European continent, stimulating and strengthening the pluralist character of EACME. Currently, about 60 centres are members of EACME, including associate members. The most important activity of EACME is the Annual Conference, organised by one of its members with support by the members of the Bureau. The conference presents an open platform for research contributions and debate about ethical issues in health care practices, policies, and biomedical sciences as well as new approaches in clinical ethics, research ethics and ethics teaching. While in the early days EACME conferences were in general meetings for senior bioethicists, the current annual conferences of EACME are offering opportunities for both senior and junior researchers to present their work to a broad international audience. The EACME specifically encourages collaboration between its member centres and offers an Exchange Programme and Collaboration Prize. To conclude, EACME has developed from a relatively closed meeting space for pioneer bioethicists towards an open and vibrant community for senior and junior researchers with the aim to develop and strengthen the discipline of bioethics in the European context. Source: EACME website: https://eacmeweb.com/